Financial planning and control systems - McGraith, Ron (1997)
This article surveys essential concepts and elements of New Zealand's state sector reforms, focusing on: the guiding philosophy - transparency and consistency; operating principles - the distinction between outputs and outcomes, purchaser and provider, government and departments, the principal instruments - purchase agreements between ministers and chief executives, delegation, performance measures. - Reproduced
Keywords: Financial administration